Estudio socioeconómico del área de influencia de la estación meteorológica convencional (CEASA UTC) de la provincia de Cotopaxi en el periodo 2020- 2021. - Pozo Sánchez, Steven Ismael (2021)
This research aimed to analyze the socio-economic influence of the conventional meteorological station CEASA-UTC Cotopaxi Province; a survey was applied to determine the degree of social influence that the station has had, an analysis of the dangers that meteorological variables may have on the area of influence was carried out to determine its direct contribution to the community. The period (2012-2019) was considered, which has the station database historical information. The estimation of missing data of the variables was obtained using the arithmetic mean method. The statistical analysis of the variables, heliophany, wind force, mean temperature, extreme temperatures, and precipitation was applied to synthesize information and provide a simple database, later the Walther-Lieth Climogram was carried out in the Restudio software that allowed to relate the temperature and precipitation variables and thus know the risks of frost, as well as the displacement of the historical data for the rainy and dry seasons. Therefore, the average temperature is 13.9 ° C, average annual precipitation, 547 mm, which corresponds to the value of 45.58 mm of average monthly precipitation. In the station, it is observed that the dry season extends from June to September, the rainy season is defined in two periods from January to May and from October to December. Also, it was verified according to the climate chart that there are no risks of frost, but there are very low temperatures that oscillate between 0.3 C and 4.4 C. The evaluation of the CEASA-UTC meteorological station let to define the importance of the use of the station to the community, reflecting in the determination of the low risk of frost and the definition of the rainy and dry seasons, which offers a tool applicable to the field and thus, to reduce the risk of agricultural production losses due to the influence of meteorological factors.